Interventions to improve liver enzyme screening testing in obese patients aged <18 years in a public hospital, Chicago, IL, 2017–2018 - Ward M; Nguyen P; Akintorin S; Arcia R; Soyemi K (Dove Medical Press, 2018)
Megan Ward,1 Peter Nguyen,1 Simi Akintorin,2 Rosibell Arcia,1 Kenneth Soyemi1,3 1Department of Pediatrics, Cook County Health, and Hospitals System, The John H. Stroger Jr. Hospital, Chicago, IL, USA; 2Keck School of Medicine, University of Southern California Medical School, Los Angeles, CA, USA; 3Department of Emergency Medicine, Cook County Health, and Hospitals System, The John H. Stroger Jr. Hospital, Chicago, IL, USA Introduction: Our study objective was to determine the health care provider liver enzyme screening testing (LEST) rates in obese pediatric patients at risk for nonalcoholic fatty liver disease (NAFLD), with the goal of improving NAFLD LEST after specific system-wide provider intervention.Methods: We conducted a bi-phased retrospective electronic medical record review of health care practitioner encounters to determine LEST in overweight/obese (body mass index≥25) patients between ages 2 and 18 years in our outpatient clinics. Intervention activities included lectures to staff and residents, fliers distributed to providers, monthly email reminders, and computer stickers placed on all terminals. From both phases, samples of simple random samples were drawn from the selected electronic medical records and reviewed for LEST screening; after intervention from this pool of patients, a random sample was chosen for LEST rate analysis. LEST rates were calculated per 100 patient encounters.Results: We screened 2,979 and 2,634 pre and postintervention pediatric encounters from which we obtained a simple random sample of patients for LEST analysis. Overall of the 264 preintervention patients, 65 (24.4%) patients received LEST translating to 24/100 encounters. Of the 65 who received screening, 53 (81%) were classified as overweight/obese. Screening rate was higher for overweight/obese patients (32/100 encounters), when compared with normal weight patients’ crude OR 3.8 (11/100 encounters; 95% CI: 1.9–7.6, P<0.005). Of the 242 postintervention patients, 70 (28%) received LEST translating to 28/100 encounters; of these, 58 (82%) were classified as overweight/obese with a rate of 42/100 encounters compared with 11/100 encounters for normal weight patients’ crude OR 5.5 (95% CI: 2.8–7.5, P<0.005).Conclusion: Obesity is a significant risk factor for NAFLD; one in four obese pediatric patients had LEST. Additional health care practitioner education and interventions are needed to improve LEST to prevent long-term complications such as liver cirrhosis or failure. Keywords: obesity, NAFLD, ALT, screening, pediatric